(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The boundary layer flow due to a surface stretching with a power law distribution in the presence of a transverse magnetic field is studied. A approximate Numerical solution for the flow problem has been obtained by solving the governing equations using Numerical Technique. A magnetic field is applied transversely to the direction of the flow. Adopting the similarity transformation, governing non linear partial differential equation of the problem are transformed to non linear ordinary differential equations. Then the numerical solution of the problem is derived using Quasilinearization method, for different values of the dimensionless parameter. The results obtained show that the flow field is influenced appreciably by the presence of chemical reaction and magnetic field.